Eski Mezopotamya’da Hukuk Kurallarının Oluşumu Sürecinde Adalet Anlayışı ve Bazı Hukuki Sorunların Çözümünde Nehir/Su Ordali Uygulaması - Öz, Esma (Fs Günbattı)
Abstract: The Justice Concept in the Process of the Formation of Legal Rules and the Application of River/Water Ordeal As a Solution of Certain Legal Problems In Ancient Mesopotamia